Word-of-Mouth Communication as a Promotional Tool in the Medical Tourism Industry - Rumyeni, Rumyeni; Samsudin, Dafrizal; Syam, Hamdani M.; Selwendri, Selwendri (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Word-of-Mouth (WOM) is an important element in marketing activities, including in the medical tourism industry. Medical tourism is the activity of traveling abroad for medical treatment. The positive experiences shared by other patients can increase patient confidence in treatment procedures and the selection of doctors and hospitals abroad. This study aims to analyze WOM communication as a promotional tool in the medical tourism industry based on the perspective of patients from Pekanbaru City who undergoing medical tourism to Malaysia. The study used a qualitative method by collecting data through in-depth interviews to 13 research informants consisting of 2 representatives from hospitals in Malaysia and 11 patients who had taken a medical tour to Malaysia. The results of the study found that in the medical tourism industry, WOM is an important element as a promotional tool seen from three aspects, namely the source of reference, the content of the message, and the credibility of the information. WOM communications for the medical tourism industry in Malaysia are sourced from references from other experienced patients, friends and family, medical practitioners and online e-WOM testimonials. The contents of WOM messages include treatment processes and procedures, medical costs, information about hospitals and doctors, as well as transportation and accommodation information. The credibility of WOM medical tourism information in Malaysia is based on information sourced from individuals who have direct experience, are recognized and trusted.